Different effects of isolation-rearing and neonatal MK-801 treatment on attentional modulations of prepulse inhibition of startle in rats - Wu, Z; Ding, Y; Jia, H; Li, L (Springer Verlag, 2016)
Rational Prepulse inhibition (PPI) is suppression of the startle reflex by a weaker sensory stimulus (prepulse) preceding the startling stimulus. In people with schizophrenia, impairment of attentional modulation of PPI, but not impairment of baseline PPI, is correlated with symptom severity. In rats, both fear conditioning of prepulse and perceptually spatial separation between the conditioned prepulse and a noise masker enhance PPI (the paradigms of attentional modulation of PPI). Objectives As a neurodevelopmental model of schizophrenia, isolation rearing impairs both baseline PPI and attentional modulations of PPI in rats. This study examined in Sprague-Dawley male rats whether neonatally blocking N-methyl-d-aspartate (NMDA) receptors specifically affects attentional modulations of PPI during adulthood. Results Both socially reared rats with neonatal exposure to the NMDA receptor antagonist MK-801 and isolation-reared rats exhibited augmented startle responses, but only isolation rearing impaired baseline PPI. Fear conditioning of the prepulse enhanced PPI in socially reared rats, but MK-801-treated rats lost the prepulse feature specificity. Perceptually spatial separation between the conditioned prepulse and a noise masker further enhanced PPI only in normally reared rats. Clozapine administration during adulthood generally weakened startle, enhanced baseline PPI in neonatally interrupted rats, and restored the fear conditioning-induced PPI enhancement in isolation-reared rats with a loss of the prepulse feature specificity. Clozapine administration also abolished both the perceptual separation-induced PPI enhancement in normally reared rats and the fear conditioning-induced PPI enhancement in MK-801-treated rats. Conclusions Isolation rearing impairs both baseline PPI and attentional modulations of PPI, but neonatally disrupting NMDA receptor-mediated transmissions specifically impair attentional modulations of PPI. Clozapine has limited alleviating effects.